KOMPENSASI DAN MOTIVASI KERJA PENGARUHNYA TERHADAP PRESTASI KERJA KARYAWAN PADA MP EVENT PLANNER MEDAN - victor, victor (Jurnal Manajemen Akuntansi Dan Administrasi Bisnis, 2021)
Employee work perfomance are influenced by the compensation and work motivation. Companies must have compensation that improves employee work performance and provides work motivation that can build employee work perfomance. The purpose of this research is to know how big influence of compensation and work motivation against employee performance at MP Event Planner medan. This research was conducted for 4(four) months, start from February 2021 until June 2021 This research uses non probability methods. Research subjects were conducted at MP Event Planner Employee with a population of 58 people. Population research using the census method. The instrument used is a questionnaire to collect data from variables of compensation, work motivation and work performance. Data analysis technique used is validity test, reliability test, descriptive analysis, normality test, multicolinearity test, heterokedastisity test, multiple linear regression analysis, T test, F Test and coefficient determination test. Descriptive analysis results in compensation and work motivation variables are in good category, and work performance variable result in very good category. The research results showed that Thitung > Ttabel, and Fhitung (191,791) > Ftabel (3,16) mean compensation and work motivation have a positive and significant impact on employee work performance at sultan iskandar muda school medan. Determination coeffisien (R2) shows that independent variables can describe employee’s performance for 71,4% meanwhile the rest of 28,6% describe by others independent variables that are excluded in this research such as leadership style, job satisfaction, comitment, comunication and others. Based of interpretation determination coeffisien guidelines, there is a significant influence between the independent variables on the dependent variables.